Abdominal Ultrasound for Surgeons - Hagopian, Ellen J.; Machi, Junji (Springer New York : Imprint: Springer, 2014)
Abdominal Ultrasound for Surgeons provides a comprehensive guide to the use of ultrasonography in surgical practice of abdominal diseases. The content is divided into three major sections focusing on basic principles of ultrasound, ultrasound anatomy and pathology of the abdomen, and employment of ultrasound of the abdomen in surgical practice. A final section is dedicated to the logistics of incorporating ultrasound into a surgical practice. The first section provides an introduction to the principles of ultrasonography focusing on ultrasound physics, equipment, and instrumentation. A detailed approach to the various scanning methods and image interpretation is demonstrated with illustrations, images, and video. The second section focuses on ultrasound anatomy of the abdomen. Each chapter demonstrates the normal and abnormal ultrasound anatomy of specific abdominal organ or organ systems (abdominal wall, liver, pancreas, biliary, stomach, anorectum, retroperitoneum, vascular) with illustrations and images. The current status and technique of endoscopic ultrasound of the upper and lower gastrointestinal tracks is addressed in this section. The third section provides a state-of-the-art review of the status of each major application of abdominal ultrasound in surgery. Topics range from trauma ultrasound and laparoscopic staging to techniques in ultrasound guidance and three-dimensional targeting. This section provides a comprehensive review of the employment of interventional, intraoperative, laparoscopic, transabdominal and endoscopic ultrasound. The fourth and last section addresses the practice aspects of incorporation of ultrasound into a surgical practice. Abdominal Ultrasound for Surgeons will serve as a very useful resource and guide for surgeons and students with little to some experience in ultrasound, including practicing surgeons, surgical fellows, and surgical residents.